EGFR amplification indicated poor prognosis in EGFR‐mutated lung cancer with leptomeningeal metastases - Di Geng; Ruina Niu; Jinghong Li; Sanxing Guo; Qianqian Guo; Siyuan Huang; Yurong Wang (The Clinical Respiratory Journal, 2024)
Abstract Background Leptomeningeal metastasis (LM) is a lethal complication of advanced lung cancer, and due to limited access to the leptomeningeal lesion, we explored the potential role of cerebrospinal fluid (CSF) as a source for liquid biopsy in LM patients of lung cancer with EGFR mutation. Materials and Methods From August 2018 to June 2021, we collected CSF samples of lung cancer patients at First Affiliated Hospital of Zhengzhou University. Next‐generation sequencing was performed to detect the mutations in EGFR genes, and 38 patients detected with EGFR mutations were finally enrolled in further clinical analyses. Results TP53 missense mutation (50%) was the most frequently detected concurrent gene in CSF. In those 10 patients whose CSF was obtained upon resistance to first TKI, TP53 missense mutation (40%, n = 4) and EGFR copy number amplification (40%, n = 4) was detected with high frequency; meanwhile, T790M mutation was found only in two patients. Known mechanisms of acquired resistance to third EGFR‐TKIs were found in 31.8% of cases. C797S or C797G mutation was identified in three patients. Possible EGFR‐independent resistant mechanism included MET amplification (4.5%), RET gene fusion (4.5%), PIK3CA missense mutation (4.5%) and CDK4 amplification (4.5%). The median OS was 55 months, the median OSLM was 38 months. EGFR amplification was associated with shortened OS in these EGFR‐mutated lung cancer with leptomeningeal metastases. Conclusion EGFR amplification indicated poor prognosis in EGFR‐mutated lung cancer with leptomeningeal metastases, providing a novel pathogenesis and treatment direction of these patients.